Comparison of the Rate of Loss of Earning Power with Disability Rate in Cases Applying to the Faculty of Medicine Department of Forensic Medicine at Ege University - Uğur Ata; Ender Şenol; Cemil Çelik (Adli Tıp Bülteni, 2021)

(untitled)
Objective:As a result of using different scales while preparing disability reports, different rates are determined for the same person. Comparing the disability rates measured by the Scales in the annex of “Capacity to Work and Vocational Permanent Disability Rates Detection Operations Regulations (CVPR)” and the Scale in the annex of “Regulation on Disability Criteria on Classification and Health Board Reports to Be Issued to the Disabled (RDC)”, this research aims at identifying differences between the scales, thereby indicating various hardships experts encounter.Methods:The cases’ gender, occupation and trauma history as well as the request letters, the injuries related to the event and the examination findings were recorded forms. After calculating each case’s profit loss rate in profession and disability rate, the components that led to different rates were evaluated.Results:It was found that following trauma, tibial, fibula and vertebral injuries occurred at most. The most frequent sequelas (52%) were a limitation of movement at a joint and a gait disorder. Since the disorders of almost half of the cases (48.1%) identified with sequela in CVPR do not appear in the A Scale, the discretionary power was enacted. Within the scope of RDC, the discreationary power was employed in 5 cases (3.1%). Average disability ratio of the cases (9.01%) appeared to be significantly lesser (p<0.05) than their average profit loss rate in profession (15.14%).Conclusion:The use of different scales under the regulation that changes according to the date of the incident leads to victimization as causing the determination of different rates due to the same sequela. Updating the scales in accordance with international standards and ensuring the conceptual unity, as a result of sharing problems and solutions regarding disability reports in joint scientific meetings held in the field of medicine and law, are important in terms of joint acceptance of the reports.